Nitrogen, Phosphorus and Potassium Status of Soils under Certain Plant Communities of Churu, Rajasthan - Sharma, B. M. (Indian Forester, 1968)
The nutrient status of the desert soils under certain plant communities of Churu, Rajasthan was determined. Nitrogen was found to vary from 0.003 to 0.336 per cent but in most of the cases it was higher at the surface. The available phosphorus ranged from 0.0625 to 0.1124 m.e. per cent. No correlation could be established between the phosphorus content and depth. The exchangeable potassium varied from 0.89 to 4.74 m.e. per cent and in most of the profiles it increased with depth. Calotropis-Calligonum community has soils richer in phosphorus and potassium, while the soils of Cenchrus-Leptadenia are richer in phosphorus and nitrogen.